Violência interpessoal juvenil e experiências individuais de conflito: jovens e adolescentes internados na ala de desintoxicação do Hospital Universitário do Oeste do Paraná - HUOP - Cristofoli, Emerson (Universidade do Vale do Rio dos Sinos, 2020)
This thesis deals with juvenile interpersonal violence and the individual experiences of conflict between young people and adolescents hospitalized in the Detoxification Ward of the Hospital Universitário do Oeste do Paraná - HUOP. The interpersonal violence of youth and adolescents is a substantial part of the set of issues that involve the problem of youth violence. This thesis demonstrates that the response can not be attributed solely to the threshold of this relationship between juvenile interpersonal violence and drug use. We proceed from this paradigm and reveal other interactions about this phenomenon, we describe different correlations in their subjective aspects, analytically observing why juvenile interpersonal violence occurs in these contexts, evaluating their meanings and their imbrications in social institutions and society. Interactions of interpersonal violence among youth and adolescents required detailed investigation. For it is not only a question of violent youthful violence, that is, barbaric or heinous crimes. There is non-fatal juvenile interpersonal violence that corresponds to injuries treated in hospital emergency services that demand an increasing recognition by researchers and professionals about the need to include violence that does not necessarily result in injury or death, but which, however, overwhelms individuals, families, communities and health care systems around the world. Given such complexity, what explains the marked presence of the phenomenon of interpersonal violence in the daily lives of young people and adolescents? In what scenarios does interpersonal violence occur? Who are your antagonists in your individual experiences of conflict? How does the HUOP Detoxification Wing institutionally exercise social control of its patients? The thesis states that juvenile interpersonal violence presents itself with one of the constituent elements of Brazilian society. This mode of violence is backed by an imaginary constructed throughout history, violent actions are continuously produced and reproduced in all social strata of Brazil. Physical, sexual or psychological violence are frequent companions of young people and adolescents, whether at home, at school or in the neighborhood in the form of mistreatment, beatings, harassment and sexual abuse. Their presence is institutionalized in relationships with all who transgress norms and values accepted as natural in societies. In this perspective, we locate the analytical and methodological framework on which this thesis is based, it is based on the production of the Sociological School of Chicago. His theorists interconnect the bases of Symbolic Interactionism as a research methodology, being this the methodological theoretical reference that provides adequate support to what this work developed in the thesis. The thesis was organized from a case study and had the combination of different procedures and research techniques with theoretical, empirical, quantitative and qualitative approaches to research.
Keywords: Violência interpessoal; Ala de desintoxicação; Jovens e adolescentes; Conflito; Interpersonal violence; Detoxification ward; Youth and adolescent; Conflict; ACCNPQ::Ciências Humanas::Sociologia